HAVING CONTACT HISTORY WITH TB ACTIVE CASES AND MALNUTRITION AS RISK FACTORS OF TB INCIDENCE: A CROSS-SECTIONAL STUDY IN NORTH SUMATERA, INDONESIA - Sitepu, Frans Yosep; Aditama, Wiwit; Depari, Elpiani (Malaysian Journal of Public Health Medicine, 2020)
Tuberculosis (TB) is one of the leading causes of morbidity and mortality. It is carrying a heavy public health problem burden in Indonesia. This study aimed to determine the risk of poor knowledge of TB, socioeconomic status, malnutrition and contact history with TB cases with the incidence of TB in Medan. This was a cross sectional study conducted between May – August 2019 in Medan municipality, in the three highest TB cases incidence public health centers (puskesmas). Structural interviews were conducted to solicit demographic data, clinical data, as well as the risk factors. Logistic regression was conducted to assess the potential risk factors associated with the infection. We enrolled 260 clinically suspected cases of TB, comprising 135 (51.9%) cases positive for TB and 125 (48.1%) cases negative for TB. In multivariate model, those who had contact history with active TB cases and those who malnourished had higher odds of having TB infection, with adjusted odds ratio (aOR): 5.58 (95%CI:3.13–9.93) and aOR: 3.36 (95%CI: 1.87–6.02), respectively. Having contact history with TB active case and malnutrition were the most significant risk factors of TB incidence in Medan municipality, North Sumatera, Indonesia. Therefore, educating patients on the importance of cough or sneezes etiquette procedures including use of face masks to minimize the risk of infection.